Access to External Finance and Manufacturing Enterprises’ Profitability in Africa:Evidence from Ethiopia - Shafi, Ajebush Argaw; Garg, Ajay K.; Muchie, Mammo (Indian Journal of Finance, 2016)
The financial sector plays a critical role in allocating capital across enterprises and industries by intermediating between creditors and lenders. The beneficial effects of the financial sector on economic activity is that access to external finance may allow firms to have better capacity to acquire necessary working capital and technical inputs that could allow small and medium enterprises (SMEs) to improve profitability performance. Therefore, financial market imperfections can reduce the efficiency of this transmission mechanism and it can have serious impact on enterprises’ real activities and harm their profitability. This study examined the effects of access to bank credit on SME profitability using evidence from the Ethiopian Central Statistics Agency (CSA) Manufacturing Industries Survey data for the period from 2005 to 2012. The study showed that access to bank credit does not affect SME profitability. Hence, the findings support the null hypothesis that bank credit has no significant effect on SMEs’ profitability improvement in Ethiopia. The findings contribute to the often contradictory and inconclusive literatures on finance and SME performance. The results are also consistent with various prior studies and pecking order theory that proposes firms will only seek external finance when they have exhausted all sources of internal finance, but it contradicts trade-off and cash flow theories.